Experimental research on the cooling performance of a new regenerative dew point indirect evaporative cooler. (November 2021) - Chu, Junjie; Xu, Wei; Fu, Yijun; Huo, Huimin
Abstract: This paper presents an experimental investigation of a new regenerative dew point indirect evaporative cooler that uses a polymer plant fibre composite material and a pure counter-flow heat exchange structure. The wet bulb efficiency, dew point efficiency and cooling capacity of the cooler were tested and analysed under various working conditions, such as a dry area, moderate humidity area and high humidity area conditions in an enthalpy laboratory. The experimental results show that the wet bulb efficiency reaches 105.6% and the dew point efficiency reaches 76% under standard drying conditions (dry-bulb temperature of 38 °C and wet-bulb temperature of 23 °C) and when the secondary air/primary air volume ratio is equal to 1.1, the cooling capacity is 2.83 kW, the dry-bulb temperature drop can reach 15.2 °C. Simulating the experimental results of the working conditions of Urumqi and a standard dry environment shows that the application of dew point indirect evaporative cooling technology in hot and dry areas has great advantages and broad application prospects. Highlights: The cooler is made of polymer plant fiber composite material, which has high-efficiency hydrophilicity. The cooler is a pure countercurrent heat exchange structure to improve the heat and mass transfer efficiency. The performance of the cooler under different environmental parameters was studied experimentally. The experimental results show that the wet bulb efficiency reaches 105.6% and the dew point efficiency reaches 76% under standard drying conditions.